A Sacrifice Zone in the Global Food Chain: The Case of Pig and Olive Production in San Pedro de Melipilla, Chile (1990-2023) - Arraño Moreno, Nicolás Ignacio (Revista de Historia Social y de las Mentalidades, 2025)
The present article analyzes the historical configuration of San Pedro de Melipilla as a sacrifice zone in the global food chain during the period 1990-2023. To achieve this, the processes of land and water appropriation and productive shifts were reconstructed. These changes, along with propelling the commune to lead the country’s pig and olive production and enabling successful international market integration for companies in these sectors, have resulted in environmental deterioration of the territory and a progressive depeasantization. The research draws on archival materials from agrarian institutions, the Registrar of Real Estate, and the General Directorate of Water, complemented by press análisis and literature.